Las cianobacterias como· indicadores de contaminación orgánica - Peinador, Mariano (1999)
In two Costa Rican rivers used as receptors for domestic sewage, treated by primary stabilization ponds, were taken a total of 28 samplings located at the pond exit and at three different sites in eachriver: 100 m before the ponds discharge, at the discharge ld 100 ni after the discharge. These s